Bridging the research-practice divide: Harnessing expertise collaboration in making a wider set of contributions. Issue 1 (March 2018) - Barrett, Michael; Oborn, Eivor
Abstract: Understanding how we develop research contributions which go beyond conversations in the academic field is an enduring challenge. While much has been written on the importance of academic-practitioner relationships in the research process more is needed on conceptualizing how we develop a wider set of contributions. In this paper, we call for researchers to be reflective as to how different forms of expertise can be drawn on during collaborative relationships to bridge the research – practice divide. We develop a framework which combines different levels of expertise with varying forms of academic-practitioner collaboration to widen the impact of our research. Four strategies are proposed by which academics may leverage their expertise in collaborative relationships with practitioners to develop Research Impact and Contributions To Knowledge (RICK). These include: maintaining critical distance, promoting deeper engagement, developing prescience, and achieving hybrid practices . We discuss implementation approaches for each of these RICK strategies and suggest writing genres to help increase engagement by practitioners in research contributions.